Case of drug-induced interstitial lung disease secondary to adalimumab. Issue 12 (23rd November 2018) - Alaee, Seema; Jones, Quentin
Abstract : In conjunction with BMJ Case Reports, DTB will feature occasional drug-related cases that are likely to be of interest to readers. These will include cases that involve recently marketed drugs for which there is limited knowledge of adverse effects and cases that highlight unusual reactions to drugs that have been marketed for several years.